Coexistence of inflammatory hepatocellular adenomas with HNF1α‐inactivated adenomas: is there an association?. Issue 6 (24th January 2014) - Castain, Claire; Sempoux, Christine; Brunt, Elizabeth M; Causse, Olivier; Heitzmann, Anne; Hernandez‐Prera, Juan C; Le, Brigitte; Schirmacher, Peter; Thung, Swan N; Balabaud, Charles; Bioulac‐Sage, Paulette
<x xml:space="preserve">Abstract</x> Aims To report the coexistence of inflammatory hepatocellular adenoma (IHCA) and HNF1α‐inactivated HCA (H‐HCA) in cases from a multicentre study. Methods and results We report nine cases with the coexistence of IHCA and H‐HCA; eight occurred in women, and one in a man. The numbers of nodules and the sizes of the largest and smallest HCAs were variable. In one case, the nodules of the two different subtypes were discovered at different times. In all women, HCAs were histologically typical, regardless of their subtype, whereas H‐HCA in the man differed histologically from classic H‐HCA. Conclusions These cases suggest that a predisposition to develop multiple adenomas, hypothetically caused by a 'benign tumorigenic field effect', although common to all HCAs, may result in different genotypes and phenotypes. Although this is rare, it is expected that more cases with the coexistence of different genotypes will emerge, owing to progress in the use of specific immunohistochemical approaches.